Use of Big Data Analytics and Sensor Technology in Consumer Insurance Context: Legal and Practical Challenges - Baris Soyer (The Cambridge Law Journal, 2022)
Insurers are increasingly utilising big data analytics and artificial intelligence in rating risks and customising insurance products particularly in consumer insurance context. The primary aim of this article is to elaborate to what extent the legal rules in force could ensure that consumers are not treated unfairly as a result of the use of such disruptive technologies. Relevant insurance law principles and doctrines are also considered as part of this analysis. The article concludes that despite the protection provided to consumers by data and consumer protection legislation, unregulated and unlimited use of data analytics and algorithms in the risk assessment process could create significant difficulties for consumers. It is argued that further regulation, especially making regular audits essential for insurers employing such technologies in risk assessment process, is required. The article also finds that the use of artificial intelligence in customising insurance products does not present similar degree of difficulties for consumers.